Removal Of Reactive Blue 19 From Aqueous Solution And Industrial Wastewater Using Activated Carbon And Iron Modified Activated Carbon - Tajudeen, Nur Farah Waheed (2019)
In this research, iron modified activated carbon (FeAC) was prepared through chemical activation method to enhance the adsorption potential of activated carbon (AC) towards the removal of Reactive Blue 19 (RB 19) dye in industrial wastewater and aqueous solution. The adsorbents were characterized by various characterization techniques such as N2 adsorption-desorption isotherm, scanning electron microscope and energy dispersion X-ray (SEM/EDX), transmission electron microscope (TEM), X-ray diffraction analysis (XRD), pH of point of zero charge (pHpzc) and Fourier transform infrared (FTIR) spectroscopy while the RB 19 industrial wastewater and aqueous solution were characterized via FTIR, Ultraviolet-visible spectroscopy (UV-Vis) and chemical oxygen demand (COD) analysis. Modification of AC surface with iron precursor decreased the surface area from 1043 to 612 m2/g while the average pore diameter increased from 1.76 to 2.42 nm. The modification of iron onto AC also resulted in a decrease in the pHpzc (5.0) compared to pHpzc of AC (7.2). The effects of various parameters such as adsorbent dosage, amount of H2O2, contact time, initial RB 19 dye concentration, pH and the reusability of the adsorbent in the presence and absence of 30 % w/w H2O2 were investigated. In the presence of H2O2, FeAC exhibited the highest removal efficiencies for RB 19 dye with 94.2 and 99.5 % in industrial wastewater and aqueous solution, respectively using 0.2 g adsorbent, 10 mL of 30 % w/w H2O2 and at ambient pH within 480 minutes.